Analisis Diagnostic Reference Level (DRL) Pasien Pada Pemeriksaan Abdomen Kontras dan Nonkontras Dengan Pesawat CT Scan Di RSUD Bali Mandara - Br Ginting, Venesia Sesilia; Sutapa, Gusti Ngurah; Ratnawati, I Gusti Agung Ayu; Widiana, I Komang (Kappa Journal, 2023)
In this study, data were obtained from 35 patients aged 27-76 years. The current used varies from 46-185 mAs and a constant tube voltage of 130 kV, with different clinical symptoms. The patient's DRL value on contrast and non-contrast abdominal examination was determined by calculating the third quartile value. On non-contrast abdominal examination, the DRL CTDIvol value was 10.62 mGy and the DLP DRL was 607.76 mGy.cm and on the non-contrast abdominal examination, the DRL CTDIvol value was 32.73 mGy and the DRL DLP value was 1825.10 mGy.cm. These results indicate that the DRL CTDI vol and DRL DLP values on contrast abdominal examination at Bali Mandara Hospital were still below the actor's limits set by BAPETEN, while on abdominal examination the DRL CTDI vol and DRL DLP values exceeded the limits set by BAPETEN. This is caused by exposure which is done three times. Therefore, it is necessary to restore both the Patient Operational Standards (SOP) and the exposure factor on an abdominal contrast CT scan at Bali Mandara Hospital.